Penguasaan Dwibahasa Di Kalangan Pelajar Tingkatan Satu - Ratna Laila, Shahidan (1998)
The purpose of this study was to identify the factors that are closely associated with the proficiency in Bahasa Melayu and English among Form One students of Hulu Perak District as measured by the independent variables such as demographic characteristic, family background, school and media factors. 277 respondents from six secondary schools in Hulu Perak District were chosen as the sample. Twelve research hypotheses were developed for this study. Statistical tools such as t-Test, ANOVA and Pearson Coefficient Correlation were used to test these hypotheses. The result of this study revealed that there were significant relationship between UPSR language subjects grade, school library's usage and television programme with the proficiency in those languages. Secondly, there were significant differences between gender and home town with the proficiency in these two languages. Thirdly, there were no significant differences between race, tuition class, parents education, parents job, mother tongue, reading materials and type of primary school with the proficiency in these two languages.